Works of Illness and the Challenges of Social Risk and the Specter of Pain in the Lived Experience of TMD. (21st October 2014) - Eaves, Emery R.; Nichter, Mark; Ritenbaugh, Cheryl; Sutherland, Elizabeth; Dworkin, Samuel F.
<x xml:space="preserve">Abstract</x> Temporomandibular Disorders (TMD) represent a particular form of chronic pain that, while not outwardly debilitating, profoundly impacts interactions as fundamental to human existence as smiling, laughing, speaking, eating, and intimacy. Our analysis, informed by an expanded "works of illness" assessment, draws attention to work surrounding social and physical risk. We refer to these as the work of stoicism and the work of vigilance and identify double binds created in contexts that call for both. Conflicting authorial stances in informants' narratives are shown to be essential in maintaining a positive identity in the face of illness. While earlier ethnographic studies report TMD sufferers' experience of stigma and search for diagnosis and legitimacy, we present a group of individuals who have accepted diagnosis at face value and soldier through pain as a fundamental aspect of their identity. [chronic pain, works of illness, risk, double binds, temporomandibular disorders]